Credit Policy and Performance of Commercial Bank in Kampala, Uganda: A Case Study of Post Bank Uganda Pbu Main Branch - Wilson Ndyagamba (Uganda Christian University, 2024)
This study examined the relationship between credit policy and commercial bank operational performance, with a focus on study contexts main branch in Kampala. The study focused on how the commercial bank's loan policy affected its financial performance. The target population was comprised of 50 workers at the study context, whereas a sample of 43 respondents was selected using Tora Yamane's method.Data was collected via questionnaires, and the results were analyzed using SPSS software. The findings reveal that respondents have a strong consensus on the influence of credit policy on the efficient performance of commercial banks. However, improved knowledge and application may lead to increased efficiency in credit evaluation and regulatory compliance. Similarly, in the study context workers reached a considerable consensus on the effectiveness of credit rules in improving financial performance, particularly in terms of implementation management and risk minimization. However, varying levels of comprehension and application demonstrate that credit rules must be refined for financial health evaluation and revenue growth.Furthermore, the research showed that approval criteria assure asset quality and that early reception is required to maximize working capital, improve profitability, and reduce the risk of default. The necessity for reliable information emphasizes the relevance of effective accounting in decision-making. Based on the findings, solutions include credit management through internet-based innovations, financial reporting through the use of computerized accounting packages, and training to improve financial management abilities in credit departments. These improvements may improve the commercial bank's financial performance and operational feasibility.